Cost-effectiveness of a vocational enablement protocol for employees with hearing impairment; design of a randomized controlled trial - Gussenhoven Arjenne HM; Anema Johannes R; Goverts S Theo; Bosmans Judith E; Festen Joost M; Kramer Sophia E (BMC, 2012)
Abstract Background Hearing impairment at the workplace, and the resulting psychosocial problems are a major health problem with substantial costs for employees, companies, and society. Therefore, it is important to develop interventions to support hearing impaired employees. The objective of this article is to describe the design of a randomized controlled trial evaluating the (cost-) effectiveness of a Vocational Enablement Protocol (VEP) compared with usual care. Methods/Design Participants will be selected with the 'Hearing and Distress Screener'. The study population will consist of 160 hearing impaired employees. The VEP intervention group will be compared with usual care. The VEP integrated care programme consists of a multidisciplinary assessment of auditory function, work demands, and personal characteristics. The goal of the intervention is to facilitate participation in work. The primary outcome measure of the study is 'need for recovery after work'. Secondary outcome measures are coping with hearing impairment, distress, self-efficacy, psychosocial workload, job control, general health status, sick leave, work productivity, and health care use. Outcome measures will be assessed by questionnaires at baseline, and 3, 6, 9, and 12 months after baseline. The economic evaluation will be performed from both a societal and a company perspective. A process evaluation will also be performed. Discussion Interventions addressing occupational difficulties of hearing impaired employees are rare but highly needed. If the VEP integrated care programme proves to be (cost-) effective, the intervention can have an impact on the well-being of hearing impaired employees, and thereby, on the costs for the company as well for the society. Trial registration Netherlands Trial Register (NTR): NTR2782